Voicing discrimination as a diagnostic marker of developmental language disorder - Georgiou, Georgios P.; Theodorou, Elena (My University, 2025)
This study examines how children with developmental language disorder (DLD) discriminate voiced and voiceless consonants and their processing speed. It also explores the contribution of factors like age, nonverbal intelligence, vocabulary, morphosyntactic skills, and sentence repetition in explaining speech perception abilities. Fourteen Cypriot Greek children with DLD and 14 peers with typical development (TD) aged 7; 10–10; 4 were recruited. Children were divided into four groups based on age and condition: young-DLD, young-TD, old-DLD, and old-TD. All children participated in an AX task, which measured their ability to discriminate sounds and their processing speed. They also completed a nonverbal intelligence test and a DVIQ test, which provided measures of various language abilities. The results demonstrated that the young-DLD group exhibited lower performance in discriminating consonants compared to the young-TD group, while such differences were not observed between the old-DLD and old-TD groups. Furthermore, while no significant differences in processing time were found between the DLD and TD groups, both young DLD and TD groups displayed longer processing times compared to their older counterparts. Age was the best-contributing factor to speech perception abilities in children with DLD in contrast to morphosyntax and vocabulary for children with TD. These findings highlight the role of voicing discrimination as a diagnostic marker of DLD as opposed to reaction time. Moreover, they underscore the crucial role of age in detecting DLD. The language developmental trajectories of children with TD appear distinct from those with DLD, as evidenced by variations in contributing factors between the two groups. These disparities can be attributed to the diverse nature of the DLD population, the therapies they receive, the compensatory strategies they employ, and the potential impact of other contributing factors.
Keywords: Consonants; Processing speed; Developmental language disorder; Speech perception